Student Cognitive Profile with STEM Based Teaching Material on the Subject of Vibrations and Waves - Rachma Afifah; Ellianawati Ellianawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
The results of study Trends in International Mathematics and Science Study (TIMSS) 2011 at the secondary school level showed that the achievement of learning outcomes of Indonesian students in the fields of mathematics and science had not shown satisfactory results. One way to implement effective and enjoyable learning can be supported by teaching materials used in learning. Teaching materials are one of the supporting factors for student learning success. This study aims to produce products and apply teaching materials based on Science, Technology, Engineering, and Mathematics (STEM) to determine the profile of the cognitive process of understanding the concepts of vocational students. The method used in this study is research and development. Characteristics of STEM-based teaching materials that contain material about vibrations and waves associated with STEM aspects and equipped with problems and practical procedures. The results of the analysis of teaching materials can be categorized as feasible, with a percentage of 78.46%. The results of the analysis of student responses after the application of the teaching materials were obtained with a percentage of 83.74% so that it can be concluded that the teaching material included in the category is very practical to use. The results of the cognitive profile analysis of students' understanding of concepts obtained an interpretation percentage of 76.06%; exemplifying 84.44%; inference 67.78%; comparing 62.59%; explain 59.89%.